Improving the specimen referral system in Ghana: findings from a landscape assessment - Nkrumah, Christopher; Forson, Paa Kobina; Nkrumah, Bernard; Owusu, Richard; Musah, Mohammed Aminu Andrew; Ahiataku, Doreenda Enyonam; Boateng, Gifty; Nanka-Bruce, Pearl; Asiedu-Bekoe, Franklin; Gudjinu, Horlali Yao; Mills-Pappoe, William Addo; Ayivase, John T.; et al. (Frontiers in Public Health, 2025)
IntroductionGhana's specimen referral system (SRS) is driven by vertical surveillance programs and outbreak response events; the lack of integration limits public health disease surveillance capacity. We assessed the current state of the SRS, the existence of biosafety, biosecurity guidelines, and the turnaround time (TAT) from sample collection to result return.MethodsWe conducted a cross-sectional survey using the African Society for Laboratory Medicine (ASLM) specimen referral tool in nine regions. A total of 265 health facilities were selected using multistage sampling. Surveillance officers, health directors, laboratory scientists, and specimen transporters were purposively selected for interviews. Also, records on SRS performance were reviewed.ResultsA hub-and-spoke system was used to transport specimens from collection points to laboratories for the HIV and TB programs. A two-way system was used to transport specimens for infectious diseases under surveillance. Within these systems, motorbikes, trucks, and mini-vans were used to transport specimens. Results were tracked using phone calls, referral logs, and the Surveillance Outbreak Response Management and Analysis System (SORMAS); results were mainly returned electronically (61.8%; 123/199). Health management teams (HMT) at regional and district health directorates (DHDs) had packaging guidelines or standard operating procedures (SOPs) for biological specimens (66%; 88/133) and had trained healthcare workers on how to transport specimens (59%; 79/133). Only 28% (55/199) of referring facilities had these guidelines/SOPs, and 45% (90/199) had at least one health worker trained in specimen packaging. Futhermore, the availability of triple-packaging materials was limited at all levels of the healthcare system, transport companies did not have guidelines/SOPs for handling specimens, and transporters were not trained on specimen handling. All reference laboratories had the necessary guidelines/SOPs. The average TAT for all specimens was 12 days, with delays occurring at collection facilities.DiscussionGhana has many pathways for transporting specimens within the disease surveillance system at no cost to patients; however, notable weaknesses exist. Inadequate resources for transportation and lack of adherence to biosafety guidelines remain major challenges. These inefficiencies in the SRS could impact the timely detection and response to health threats and may increase the risk of diseases spreading within and beyond Ghana's borders.